CellNet Data Systems to Add 450,000 Meters to AmerenUE Network for Total Of 1.3 Million Meters (PR Newswire, 1998)
SAN CARLOS, Calif., April 27 /PRNewswire/ -- CellNet Data Systems, Inc. (Nasdaq: CNDS), a market-leading provider of fixed-network wireless information services, and AmerenUE, an operating company of Ameren Corporation (NYSE: AEE), today announced the signing of a Memorandum of Understanding to expand CellNet's network for AmerenUE by 450,000 meters in order to provide Network Meter Reading (NMR) services to AmerenUE's Missouri customers outside of metropolitan St. Louis. Subject to final contract agreement, deployment of the expanded network for AmerenUE is scheduled to begin in the fall of 1998. When fully deployed, the total network for AmerenUE will provide coverage for approximately 1.3 million meters. The expanded network for AmerenUE will be CellNet's first rural network, providing coverage over a 24,000 square-mile area. CellNet now operates and is completing the deployment of an 800,000-meter network for AmerenUE in the metropolitan St. Louis area. This network is currently the largest of its kind in the world with a total of approximately 600,000 electric and natural gas, residential, commercial and industrial meters online.